(untitled) (diségno, 2019)
I started drawing at the age of five, a time when I always had pieces of paper and pencils in my hands, and I used to draw the most bizarre, the funniest things that came to my mind. I remember that I used to enjoy making objects look like humans, such as, for example, small funnels that I added human legs and arms to; funnels that filled themselves with water from the top, making it come out at the bottom. (read more)